An optimized robotic surgical technique for cervical cancer: investigating whether the use of the pulling robotic arm has better surgical outcomes - Liang, Xuzhi; He, Haijing; Li, Yingjin; Chen, Sibang; Zhao, Jinche; Yang, Bing; Lin, Huisi; Zeng, Hao; Wei, Liuyi; Yang, Jiahuang; Fan, Jiangtao (Frontiers in Oncology, 2023)
Objective: The evidence for adopting the 3rd robotic arm (RA) called the pulling RA rather than a uterine manipulator to manipulate the uterus in the robotic radical hysterectomy (RRH) for cervical cancer is still limited. We present a single-center retrospective experience comparing using the pulling RA to replace a uterine manipulator vs. using a uterine manipulator to manipulate the uterus in RRH. Methods: 106 patients diagnosed with IA, IB1-IB2 and IIA1 cervical cancer were retrospectively included for intraoperative and postoperative parameters analysis. 50 patients received RRH by adopting the pulling RA instead of a uterine manipulator to pull the uterus (3-RA RRH group), and another 56 patients were performed RRH with a uterine manipulator (2-RA RRH group). RRH with the pulling RA consisted of a camera arm, 3 RAs including a pulling RA, and 2 conventional assistant arms (3-RA RRH group). In comparison, RRH with a uterine manipulator included 2 RAs and 2 conventional assistant arms (2-RA RRH group). Besides, 3-RA’ RRH group was selected from the 25th-50th cases in the 3-RA RRH group based on the learning curve and was compared with the 2-RA RRH group in terms of intraoperative and postoperative parameters. Results: The patients’ early post-operative complication (≤7 days) (p=0.022) and post-operative anemia (p < 0.001) of the 3-RA RRH were significantly lower than that in the 2-RA RRH group. The results of comparing the 2-RA RRH group with the 3-RA’ RRH group were consistent with the aforementioned results, except for the operative time (220.4 vs. 197.4 minutes, p=0.022) and hospital stay (7.8 vs. 8.7 days, p=0.034). The median follow-up in the 3-RA RRH and 2-RA RRH groups was 29 and 50 months till March 2023. The 3-RA RRH and 2-RA RRH groups' recurrence rates were 2% (1/50) and 5.4% (3/56), respectively. The mortality in the 3-RA RRH and 2-RA RRH groups was 2% (1/50) and 3.5% (2/56), respectively. Conclusions: Our study suggested that replacing the uterine manipulator via the 3rd RA is viable; the results showed comparable surgical outcomes between the two methods. Thus, 3-RA RRH could be considered a well-executed surgical option in well-selected patients.